Residual Syntax Score as a Predictor of 30-Day Mortality after Primary Percutaneous Coronary Intervention for Acute ST-Elevation Myocardial Infarction - Khawar Naeem Satti, Muhammad Mohsin, Amina Ijaz, Atif Nazir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate residual SYNTEX score as a predictor of 30-day mortality after primarypercutaneous coronary intervention (P-PCI) in ST-elevation myocardial infarction (STEMI) patients. Methodology: It was a quasi-experimental study conducted in the Emergency department of Rawalpindi Institute of Cardiology from September 2019 to September 2020. After the study approval from the ethics committee and informed consent, 200 patients presenting with acute STEMI were included by convenient sampling. Primary PCI was done in all patients by theconsultant cardiologists, and then the residual SYNTEX score (rSS) was calculated for each patient. Patients were allocated the case or control group based on rSS: patients with complete revascularization were included in controls and those with incomplete revascularization were labeled as cases. All patients were followed after primary PCI for 30-day mortality. The analysis of data was carried out by the Statistical Package for Social Sciences (SPSS) version 25. Results: The 30-day mortality occurred in 11(5.5%) patients. Mortality occurred in 9(4.5%) patients in the case group and 2(1%) patients in the control group with a significant p-value of 0.03There was a significant association between diabetes mellitus & 30-day mortality (0.032) and a family history of ischemic heart disease & 30-day mortality (0.026). This shows that rSS can be used as a reliable predictor of 30-day mortality after P-PCI in STEMI patients. The patients with high rSS score and risk factors of diabetes mellitus and history of ischemic heart disease are at higher risk of 30-day mortality. Conclusion: The residual Syntax score is a simple, reliable and significant marker of 30-day mortality after P-PCI in STEMI patients. It provides an accurate assessment of the extent of revascularization needed to prevent coronary artery disease and enhance the prognosis following P-PCI. It may also serve as a guide for additional PCI decisions. Keywords: Residual Syntax score; rSS; Primary percutaneous coronary intervention;Acute ST-elevation myocardial infarction; STEMI; P-PCI